Crataeva nurvala nanoparticles inhibit virulence factors and biofilm formation in clinical isolates of Pseudomonas aeruginosa. (22nd November 2016) - Ali, Syed Ghazanfar; Ansari, Mohammad Azam; Khan, Haris M.; Jalal, Mohammad; Mahdi, Abbas Ali; Cameotra, Swaranjit Singh
Abstract : Green synthesized nanoparticles have gained great attention due to their non‐toxic and non‐hazardous nature. In the present study, bark extract of the medicinal plant in Ayurveda Crataeva nurvala (Buch–Ham) (CN) was chosen for the biosynthesis of silver nanoparticles (AgNPs). These NPs were characterized by Ultra violet visible spectroscopy, Fourier Transform Infra Red, Atomic Force Microscopy, and Transmission Electron Microscopy (TEM). The average particle size of green synthesized CN‐AgNPs was 15.2 ± 1.01 nm. Gas chromatography‐ mass spectrometry analysis of methanolic bark extract involved in the formation of CN‐AgNPs revealed lupeol as a major active component. In this study, CN‐AgNPs (15 μg ml −1 ) efficiently suppressed the production of quorum sensing mediated virulence factors viz. pyocyanin, protease, hemolysin, and biofilm formation in Pseudomonas aeruginosa . The pyocyanin production was strongly inhibited (74.64%) followed by proteolysis (47.3%) and hemolysin production (47.7%). However, the biofilm forming ability was maximally reduced up to 79.70%. Moreover, the Confocal Laser Scanning Microscopic Analysis showed that CN‐AgNPs inhibit colonization of P. aeruginosa on to the surface. Furthermore, TEM analysis revealed internalization of CN‐AgNPs inside the bacterial cell. It is concluded that green synthesized AgNPs have great potential to inhibit virulence factors and biofilm forming ability of drug‐resistant clinical isolates of P . aeruginosa .